THE ISSUE OF METHODOLOGICAL ASPECTS OF ASSESSMENT OF LAND RESOURCES - Dauzova, А.М.; Dyrka, S. (Academic Journal of Physical and Chemical Sciences, 2018)
Basis of formation of effectively functioning agricultural production is improvement of the land relations and formation of system of land use, “adequate market economy”. Society hasthe great need in transition to essentially new type of economic growth - to the intensive growth of resource-saving type, based on careful use of natural resources, on achievement of ecological equilibrium. In life of society the earth has special, outstanding value. It is the most important condition of existence of mankind, irreplaceable means of satisfaction of the most different requirements: economic, social, esthetic, etc. However, speaking about use of the earth, usually mean its functioning in the sphere of production. Rational use of land resources has the great importance in rural economics and the countries, all over the world. In the spheres of production activity of the person the role of the earth isn’t identical. In the industry, transport and cities constructions wereused the base, spatial operational basis for the production placement. More particularly important the earth becomes in mining industry, where it serves as a raw materials source. The process of production and receiving results of production don’t depend on the quality of the soil, relief and many other properties, inherent in the earth.